Building Public Trust in Islamic School through Adaptive Curriculum - Hasan Baharun; Abd Hamid Wahid; Chusnul Muali; Fathor Rozi; Muhammad Wahyu Fajry (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
This study aims to investigate an adaptive curriculum serving as a medium to build public trust at Islamic Elementary School (SDI) Tompokersan Lumajang, East Java. It is qualitative using phenomenological methods. Data were collected using interview, observation and documentation techniques. They were analyzed through several steps: data collection, data reduction, data presentation and conclusions. The results showed that the implementation of an adaptive curriculum was done by optimizing the role of school committees, developing excellent school, offering variations in extracurricular activities to motivate students, and providing counseling guidance programs. This research suggests the importance of innovation in delivering education to meet the social dynamics and global change.